Success of Cochlear Implantation in patients after bacterial meningitis - Guincho, Joana (2024)
Aim: To present the results of cochlear implantation after bacterial meningitis, regarding auditory gain, time of use and improvement in quality of life. Material and Methods: Retrospective, transversal study, based on the analysis of data from patients with severe and profound sensorineural hearing loss due to bacterial meningitis, who underwent uni or bilateral cochlear implant surgery at CHLO between 2014 and 2022. Results: The sample included 13 patients. Four had cochlear ossification. The insertion of electrodes in the cochlea was total, except for 1 case. Six ears achieve 100% intelligibility. No relationship was found between cochlear ossification and intelligibility. Conclusion: Auditory rehabilitation with cochlear implants in this group of patients is effective, improving levels of intelligibility and quality of life, even in cases of late referral and in the presence of fibrosis/partial ossification of the cochlea.